Pelaksanaan Batuk Efektif Pada Pasien Tuberkulosis Paru Di Wilayah Kerja UPTD Puskesmas Puhjarak Kecamatan Plemahan Kabupaten Kediri - Rahmad Karyanto; Nurul Laili (STIKES Karya Husada Kediri, 2018)
Tuberculosis is a infection disease attacking parenchyme of lungs. Tuberculosis can spread to another parts of our body, as kidney, bone and nodus limfe. Infection agent is Mycobacterium tuberculosis. Cough is an act that needed for cleaning secret. Aim of research is to know how to do an effective cough for tuberculosis patient at UPTD Puskesmas Puhjarak Plemahan District Kediri City. The method that being used in this research is descriptive. Sample are 11 respondents. This research use “Total Sampling”. Variable of the research is effective cough to tuberculosis patients and collecting data by using interview form. The result is got from 11 respondents, most of half patients (5 respondents/46%) do effective cough less, most of half patients (4 respondents/36%) do effective cough enough and few patients (2 respondents/18%) do it well. Doing effective cough is influenced by education degree, respondents desire to be healthy and come to clinic to check regulary. It is expected that the patient to carry out effective cough with the right and expected officers to improve the quality of nursing services to patients with Pulmonary Tuberculosis